Raspiblocos: ambiente de programação didático baseado em Raspberry Pi e Blockly - Heinen, Eduarth (2015)
This project details a visual programming environment able to translate instructions, represented by building blocks, into actions performed by components of a concrete robotic model. The environment’s interface was implemented with Blockly library, and the robotic model with the single board computer Raspberry Pi. As a differential technology, it is an open-source initiative where the same piece of hardware acts as a host for a web application, accessible through wifis, and as a controller of the electronic components. With this, the experiments can be easily replicated. The tool provides experiments in programming and robotics build by the students acting as a motivational and enhancement factor in learning.